2020
DOI: 10.1155/2020/8841127
|View full text |Cite|
|
Sign up to set email alerts
|

Statistical Analysis for Identifying Differentially MicroRNA in Serum Exosomes of Lead Workers

Abstract: Exosomes can transmit central nervous system (CNS) information to the peripheral circulatory system through the brain barrier, and exosomes in the blood can also enter the central nervous system likewise. The components of exosomal contents play a pivotal role in cell signal communication, and thus, the transmission of exosomal content components is considered as a newly discovered method of long-distance communication between cells. The current is aimed to explore the changes of the exosomal microRNA group in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%